Implementasi Metode Overall Equipment Effectiveness (OEE) untuk Meningkatkan Produktivitas Mesin Press - Muyasar, Athariq Dias; Ngudi Wiyatno, Tri; Indra Prasetya, Dwi (Prosiding Sains dan Teknologi, 2024)
As a ceramic tile manufacturer that has quite high demand, companies are required to meet consumer demand in a timely manner, so production must optimize what is used in the production process. Based on the results of observations, the company experienced a decline in productivity in the Press Machine unit. One of the causes of waste is low productivity during the production process caused by machine factors. One method that can be used to increase machine efficiency is the Overall Equipment Effectiveness (OEE) method. The results of calculating the OEE percentage in 2022 are 83.47%, with Availability value 93.73%, Performance 91.79%, Rate of Quality 97.20%, One of the reasons why the OEE percentage is not optimal is because the machine performance ratio is still low, especially the performance in March 2022, which is 89.68%, while the % of six big losses is 18.62%, the most dominant component of six big losses on Press machines is reduced speed losses of 8.21% with man, machine, material and method factors as factors that cause reduced speed losses to still be high, recommended To improve reducing speed loss, this includes conducting training for employees, especially regarding filling in the machine's Daily Check Sheet, training on abnormality rules and training on making daily book.